The effect of monetary policy on inflation heterogeneity along the income distribution - Miguel Ampudia; Michael Ehrmann; Georg Strasser (European Central Bank (ECB), 2023)
This paper studies the effect of monetary policy on inflation along the income distribution in several euro area countries. It shows that monetary policy has differential effects and identifies two channels which point in opposite directions. On the one hand, different consumption shares imply that inflation by high-income households responds less to monetary policy. On the other hand, the paper provides novel evidence that there are substantial differences in shopping behaviour and its reaction to monetary policy, which imply that inflation by high-income households responds more to monetary policy.
Keywords: E31; E52; D30; 330; inflation; distributional effects; monetary policy; shopping behaviour; substitution